PEMBERDAYAAN PEREMPUAN MELALUI SEKOLAH PEREMPUAN DI KABUPATEN GRESIK - Bagus Ananda Kurniawan; Nur Fitri Ana Melati (Jurnal Gesi, 2022)
The Gresik Regency Government through the Office of Family Planning, Women's Empowerment and Child Protection (KBP3A) has a breakthrough program for women's empowerment from 2018 to 2021 by establishing a women's school as a means of publishing commitments from the Gresik Government in increasing the empowerment of marginalized women through the Women's School. Besides that, one of the reasons why this activity is important is so that the public also knows the commitments that have been made by the local government and village governments towards improving the strategic position of women, especially the success of the Women's School program. in Gresik district by inaugurating 10 Women's Schools located in new areas. Empowerment through women's schools is carried out by making women aware of their rights and providing counseling to village women about gender education. In addition, girls' schools provide village women with the ability to confidently convey their aspirations to their families and communities. The results obtained by members of being a women's school are, getting a lot of knowledge about gender equality and gender fair education for women, gaining knowledge about village laws, so that women can also play a role in rural welfare development.